Pengaruh Kompensasi Eksekutif, Koneksi Politik, dan Capital Intensity terhadap Tax Avoidance - Cindy Felicia Nainggolan; Maulana Malik Muhammad (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Tax avoidance is an engineering tax affairs in legal way by obeying and not going out from the regulations. This study aims to determine the effect of executive compensation, political connections, and capital intensity on tax avoidance measured using Cash Effective Tax Rate (CETR). The population in this study is manufacturing companies listed on Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample selected is 243 companies which selected by purposive sampling method. This study uses a classic assumption test, model feasibility test, multiple linear regression analysis and hypothesis test with data processing Eviews 10. The result of the research shows that executive compensation has no significant effect on tax avoidance, political connections has a positive and significant effect on tax avoidance and capital intensity has a negative and significant effect on tax avoidance.